2016
DOI: 10.1016/j.abb.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol improves dysfunctional glucose and lipid metabolism in diet-induced obese C57BL/6J mice

Abstract: Xanthohumol (XN) is a prenylated flavonoid found in hops (Humulus lupulus) and beer. The dose-dependent effects of XN on glucose and lipid metabolism in a preclinical model of metabolic syndrome were the focus of our study. Forty-eight male C57BL/6J mice, 9 weeks of age, were randomly divided into three XN dose groups of 16 animals. The mice were fed a high-fat diet (60% kcal as fat) supplemented with XN at dose levels of 0, 30, or 60 mg/kg body weight/day, for 12 weeks. Dietary XN caused a dose-dependent decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 53 publications
3
86
3
Order By: Relevance
“…In vivo studies: XN has been shown in many animal models to have anti-obesity properties [3,[31][32][33][34]. Miranda et al, demonstrated in a mouse model with a high fat diet, that XN 30-60 mg/kg was able to lower plasma LDL by 80%, interleukin-6 by 78%, as well as other pro-lipid enzymes also reduced by more than 40% compared to control [34]. The same group found that XN and its hydrogenated derivatives α, β-dihydro-xanthohumol (DXN) and tetrahydro-xanthohumol (TXN) improved glucose tolerance as well as cognitive function in mice fed with high fat diet.…”
Section: Benefits Of Xanthohumol In Hyperlipidaemia Obesity and Typementioning
confidence: 99%
“…In vivo studies: XN has been shown in many animal models to have anti-obesity properties [3,[31][32][33][34]. Miranda et al, demonstrated in a mouse model with a high fat diet, that XN 30-60 mg/kg was able to lower plasma LDL by 80%, interleukin-6 by 78%, as well as other pro-lipid enzymes also reduced by more than 40% compared to control [34]. The same group found that XN and its hydrogenated derivatives α, β-dihydro-xanthohumol (DXN) and tetrahydro-xanthohumol (TXN) improved glucose tolerance as well as cognitive function in mice fed with high fat diet.…”
Section: Benefits Of Xanthohumol In Hyperlipidaemia Obesity and Typementioning
confidence: 99%
“…Hop (Humulus lupulus L. var lupulus) is a diploid (2n = 2x = 18 ? XX/XY) dioecious perennial crop species used principally for beer bittering and flavoring although alternate uses include replacement of antibiotics in poultry (Bortoluzzi et al 2014), anticancer (Miranda et al 1999;Jiang et al 2018), metabolic disorder (Miranda et al 2016) and estrogen replacement therapy (Hemachandra et al 2012). It is produced on six meters tall trellis under wide row spacing (three to five meters) between rows in most countries with the exception of Great Britain where some hops are produced under 2.5 m low-trellis using hops bred specifically for these conditions (Neve 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Hop (Humulus lupulus L var lupulus) is a diploid (2n=2x=18 + XX/XY) dioecious perennial crop species used principally for beer bittering and flavoring although alternate uses include replacement of antibiotics in poultry (Bortoluzzi et al, 2014), anti-cancer (Miranda et al, 1999, Jiang et al, 2018, metabolic disorder (Miranda et al, 2016) and estrogen replacement therapy (Hemachandra, et al, 2012). It is produced on six meters tall trellis under wide row spacing (three to five meters) between rows in most countries with the exception of Great Britain where some hops are produced under 2.5 m low-trellis using hops bred specifically for these conditions (Neve, 1991).…”
Section: Introductionmentioning
confidence: 99%